(untitled) (Colombia Medica, 2020)
Introduction: The low frequency of cases and deaths from the SARS-CoV-2 COVID-19 virus in some countries of Africa has called our attention to the unusual behavior of this disease. Aims: Describe SARS-CoV2 infection and death rates in African countries that participated in an intensive Ivermectin mass campaign carried out to control onchocerciasis and compare them with those of countries that did not participate. Methods: Data from 19 countries that participated in the WHO sponsored African Programme for Onchocerciasis Control (APOC), from 1995 until 2015, intended to treat over 90 million people annually and protect an at-risk population of 115 million, were compared with thirty-five (Non-APOC), countries that were not included. Information was obtained from https://www.worldometers.info/coronavirus/ database. Results After controlling for different factors including the Human Development Index, APOC countries, show statistically significant 28% lower mortality (0.72 IC 95% 0,67-0,78) and 8% lower rate of infection (0.92 IC95% 0,91-0,93) due to COVID-19. Conclusions: The incidence in mortality rates and the number of cases is significantly lower among the APOC countries compared to non-APOC countries. That a mass public health preventive campaign against COVID-19 may have taken place, inadvertently, in some African countries with massive community ivermectin use is an attractive hypothesis. Additional studies are needed to confirm it.